OK-432 Acts as Adjuvant to Modulate T Helper 2 Inflammatory Responses in a Murine Model of Asthma - Cheng-Jang Wu; Pin-Hsun Tseng; Cheng-Chi Chan; Sara Quon; Li-Chen Chen; Ming-Ling Kuo (Journal of Immunology Research)
Enhanced type 2 helper T (Th2) cell responses to inhaled harmless allergens are strongly associated with the development of allergic diseases. Antigen formulated with an appropriate adjuvant can elicit suitable systemic immunity to protect individuals from disease. Although much has been learned about Th1-favored immunomodulation of OK-432, a streptococcal preparation with antineoplastic activity, little is known about its adjuvant effect for allergic diseases. Herein, we demonstrate that OK-432 acts as an adjuvant to favor a systemic Th1 polarization with an elevation in interferon- (IFN-) γ and ovalbumin- (OVA-) immunoglobulin (Ig) G2a. Prior vaccination with OK-432 formulated against OVA attenuated lung eosinophilic inflammation and Th2 cytokine responses that were caused by challenging with OVA through the airway. This vaccination with OK-432 augmented the ratios of IFN-γ/interleukin- (IL-) 4 cytokine and IgG2a/IgG1 antibody compared to the formulation with Th2 adjuvant aluminum hydroxide (Alum) or antigen only. The results obtained in this study lead us to propose a potential novel adjuvant for clinical use such as prophylactic vaccination for pathogens and immunotherapy in atopic diseases.